Sonic Hedgehog Signaling in Primary Culture of Human Corpora Cavernosal Tissue from Prostatectomy, Diabetic, and Peyronie's Patients. Issue 8 (23rd June 2022) - Martin, Sarah; Deng, Jiangping; Searl, Timothy; Ohlander, Samuel; Harrington, Daniel A.; Stupp, Samuel I.; Dynda, Danuta; McVary, Kevin T.; Podlasek, Carol A.
ABSTRACT: Background: Cavernous nerve (CN) injury causes penile remodeling, including smooth muscle apoptosis and increased collagen, which results in erectile dysfunction (ED), and prevention of this remodeling is critical for novel ED therapy development. Aim: We developed 2 peptide amphiphile (PA) hydrogel delivery vehicles for Sonic hedgehog (SHH) protein to the penis and CN, which effectively suppress penile distrophic remodeling (apoptosis and fibrosis), in vivo in a rat CN injury model, and the aim of this study is to determine if SHH PA can be used to regenerate human corpora cavernosal smooth muscle deriving from multiple ED origins. Methods: Corpora cavernosal tissue was obtained from prostatectomy, diabetic, hypertension, cardiovascular disease and Peyronie's (control) patients (n = 21). Primary cultures (n = 21) were established, and corpora cavernosal cells were treated with SHH protein, MSA (control), 5E1 SHH inhibitor, and PBS (control). Growth was quantified by counting the number of cells at 3–4 days. Statistics were performed by ANOVA with Scheffe's post hoc test. Concentration of SHH protein for maximal growth was optimized, and a more active SHH protein examined. Outcomes: Cultures were characterized by immunohistochemical analysis with ACTA2, CD31, nNOS and P4HB, and smooth muscle was quantified in comparison to DAPI. Results: Cultures established were >97% smooth muscle. SHH protein increased growth of smooth muscle cells from prostatectomy, diabetic, and Peyronie's patients in a similar manner (49%–51%), and SHH inhibition decreased growth (20%–33%). There was no difference in growth using 25 ug and 10 ug SHH protein, suggesting a threshold concentration of SHH protein above which smooth muscle growth is enhanced. A more active lipid modified SHH peptide further enhanced growth (15%), indicating a more robust growth response. SHH increased growth in smooth muscle cells from hypertension (37%) and cardiovascular disease (32%) patients. SHH protein increased growth under normal and high glucose conditions, suggesting that high glucose conditions that may be present in under controlled diabetic patients would not detract from SHH regenerative capacity. Clinical Implications: SHH PA would be beneficial to enhance smooth muscle regeneration in patients with ED of multiple etiologies. Strengths and Limitations: Understanding how human corpora cavernosal tissue responds to SHH treatment is critical for clinical translation of SHH PA to ED patients. Conclusion: Corpora cavernosal smooth muscle from all ED patients responded to SHH treatment with increased growth.